Efficacy of Adjuvant Systemic Chemotherapy Combined with Radical Surgery and Hyperthermic Intraperitoneal Chemotherapy in Gastric Cancer Treatment - Reutovich, M. Yu. (Indian J Surg Oncol, 2020)
Evaluation of the efficacy of the combination of radical surgery, hyperthermic intraperitoneal chemotherapy (HIPEC), and adjuvant systemic chemotherapy (ACT) in reducing gastric cancer progression in patients with resectable serosa-invasive gastric cancer in a single institution. In 2015–2016, 19 patients with gastric cancer (stage IIB-IIIC) were included in the trial. The trial protocol comprised radical surgery, HIPEC (cisplatin 50 mg/m(2) + doxorubicin 50 mg/m(2), 42 °C, 1 hour), and 1–8 cycles of ACT (oxaliplatin 100 mg/m(2) administered on day 1 of each cycle and oral capecitabine 1000 mg/m(2) (or tegafur 10–15 mg/kg) administered twice daily on days 1–14 of each cycle with an interval of 7 days between cycles). Following the ACT treatment, the patients were divided into 2 subgroups—those who underwent up to 6 ACT cycles (1–6 cycles, subgroup ≤ 6–8 patients) and those who underwent 7–8 ACT cycles (subgroup > 6–11 patients). Three-year metastasis-free survival (MFS) for the > 6 subgroup was 91 ± 9%. With a follow-up median of 17 months, 3-year MFS for the ≤ 6 subgroup was not reached − p(log-rank) = 0.003. The trial showed that in managing advanced gastric cancer patients (pT4a-4bN0-3 M0) by supplementing radical surgery with ACT-enhanced hyperthermic intraperitoneal chemotherapy, ACT proved to be highly effective when administered in its full mode of 7–8 cycles compared with its truncated variant of 1–6 cycles.